French spirit today : University of Southern California, Fisher Art Gallery, Los Angeles, March 19-April 21, '84 ; Museum of Contemporary Art, La Jolla, June 16-August 3, '84. - Fisher Gallery (University of Southern California); La Jolla Museum of Contemporary Art. (Los Angeles : Fisher Gallery, 1984)
"The USC exhibition which is the first of these shows, deliberately points to the aspect of "Cultural content" and not to that of "spectacle" which is of primal importance to us. Thus, the californian public will meet the french artists of the younger generation through more personal and more secret expressions: notes of work, diaries, plans and projects, models and of course drawing as a specific expression..."
Includes bibliography.
Keywords: Artet boterore; Arti vizual; Arti bashkekohor; Art, French -- Exhibitions-ekspozite; Art, French -- 20th century-shekulli i 20-te -- Exhibitions-ekspozite; Arti francez; Artiste franceze-piktura-fotografia-instalacioni